Embracing Diversity: Understanding School Leaders Lived Experience In Supporting Teachers Handling Learners With Special Needs - Paredes, Jayeth; Montillano, Allen Cris; Pendon , Fernando T (Edu Berkah Khatulistiwa, 2025)
This transcendental phenomenological study explored the lived experiences of public elementary school heads in the Division of Cabuyao in supporting teachers who handle learners with special needs in inclusive classrooms. Anchored on the principles of inclusive education and grounded in the theories of Behaviorism-Based Inclusive Education and Social Support, the research aimed to understand the nature, challenges, and strategies of school leaders in fostering inclusive practices. Through in-depth interviews with ten school heads, the study revealed that both tangible (instructional materials, learning tools) and intangible (technical assistance, emotional support, mentoring) forms of support are essential in empowering teachers to manage inclusive classrooms effectively. The findings also highlighted significant challenges such as lack of training, limited resources, behavioral complexities of learners, and parental denial. From the thematic analysis, ten core themes emerged, including comprehensive support systems, empathetic leadership, collaborative feedback mechanisms, and the importance of continuous professional development. These insights informed the development of the Systematic Mechanism and Appropriate Response Techniques (SMART) framework—a strategic model designed to guide school heads in enhancing their support systems for inclusive education. The study concludes that sustaining inclusivity requires a holistic, collaborative, and policy-aligned approach that empowers both teachers and school leaders. It recommends strengthening partnerships with stakeholders, embedding inclusive practices in school culture, and institutionalizing continuous capacity-building initiatives.